MedBulletin - Meducator, The; Amir, Takhliq; Yu, James (The Meducator, 2019)
MedBulletins are hand-picked, at-a-glance summaries of current news and hot topics in Health, Medicine, and Biomedical Research. The aim is to keep readers up-to-date with the latest issues and breakthroughs within these diverse fields. MedBulletins are selected and written by Meducator staff on a regular basis.